Room Service: Communication Management in Handling Guest Complaints at Three-Star Hotels in Bogor - Ayu Pradnyani, Ketut; Hengky, SH (Finance : International Journal of Management Finance, 2025)
This looks at investigates the effectiveness of communication control with the aid of room service team of workers in coping with visitor lawsuits at 3-megastar hotels in Bogor. The studies adopt a quantitative survey approach, accumulating statistics from both lodge visitors and provider team of workers to seize perspectives on carrier interactions. Statistical evaluation changed into performed using SPSS, with descriptive tabulation employed to profile respondents and summarize communique practices. moreover, one-way ANOVA was implemented to have a look at the have an impact on of three key conversation control dimensions—readability, empathy, and responsiveness—on guest pleasure tiers. The findings display that clarity of facts and empathetic verbal exchange have a big fantastic effect on visitor satisfaction, while responsiveness suggests a weaker effect and suggests an area requiring managerial development. those outcomes spotlight the crucial role of effective conversation in shaping carrier recuperation effects and advise that motel management must prioritize education applications that decorate group of workers empathy and readability whilst addressing visitor concerns. by using doing so, three-famous person accommodations in Bogor can beef up client loyalty, improve service best, and stay competitive within the hospitality industry.